Analisis Komparatif Tingkat Harga dan Varian Produk Terhadap Keputusan Pembelian (Studi kasus pada minuman Tong Tji dan AMK di Surabaya) - Kartikasari, Erika; Pujianto, Agung; Maduwinarti, Ayun (Universitas 17 Agustus 1945 Surabaya, 2020)
This study aims to determine differences in prices and product variants in purchasing decisions at Tji Tong and AMK. Quantitative research methods with survey questionnaires as instruments. The consumer research population once bought Tong Tji and AMK in Surabaya. The research sample used a non-probability sampling method with a purposive sampling technique of 96 respondents. The data analysis technique used to answer hypotheses is the independent sample t test.The results showed that the independent variables, namely price and product variants, had differences in the dependent variable in purchasing decisions. The significant value of the price variable is 0.003 and the significant value of the product variant variable is 0.009 and the dependent variable is the purchase decision has a significant value of 0.007. All significant value variables smaller than 0.05 mean that the independent price variables and product variants have differences in purchasing decisions at Tong Tji and AMK.Keywords : Comparative Analysis,price,TongTji product variants,AMK.